Analyzing delinquency among Kurdish adolescents: a test of Hirschi's social bonding theory - Ziyanak, Sebahattin (Lexington Books, 2015)
Introduction -- Social bonding theory -- The Kurdish Worker Party (PKK) -- Terrorism in the name of religion -- The Gülen movement -- One in the movement and his journey -- Findings -- Discussion -- Summary and conclusions